Relative Measurement Errors in Valuing Plant and Equipment Under Current Cost and Replacement Cost. - Swanson, Edward (The Accounting Review, 1990)
Examines the advantages and suitability of the Financial Accounting Standards No. 33 (FAS 33) for calculating operating income for plant and equipment relative to the Accounting Series Release No. 190 (ASR 190) data. Current cost versus replacement cost; Measurement errors arising from inconsistent technology problem; Influential factors.